2014
DOI: 10.1007/s11427-014-4786-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo RNAi screen identifies candidate signaling genes required for collective cell migration in Drosophila ovary

Abstract: Collective migration of loosely or closely associated cell groups is prevalent in animal development, physiological events, and cancer metastasis. However, our understanding of the mechanisms of collective cell migration is incomplete. Drosophila border cells provide a powerful in vivo genetic model to study collective migration and identify essential genes for this process. Using border cell-specific RNAi-silencing in Drosophila, we knocked down 360 conserved signaling transduction genes in adult flies to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 73 publications
1
17
1
Order By: Relevance
“…Second, Src42A promotes the detachment of the cluster from the follicular epithelium and third, the limitation of the Src42A protein and activity is required in order to maintain the morphology and integrity of the cluster during collective cell migration. While previous studies have shown that constitutive activation of Src42A impedes border cell migration (Luo et al, 2015;Somogyi and Rørth, 2004), we show the requirement for, and the pattern of activity of, Src42A during this process.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Second, Src42A promotes the detachment of the cluster from the follicular epithelium and third, the limitation of the Src42A protein and activity is required in order to maintain the morphology and integrity of the cluster during collective cell migration. While previous studies have shown that constitutive activation of Src42A impedes border cell migration (Luo et al, 2015;Somogyi and Rørth, 2004), we show the requirement for, and the pattern of activity of, Src42A during this process.…”
Section: Discussioncontrasting
confidence: 55%
“…Over-expression of Src WT results in a large increase and ectopic localization of active Src in border cells, suggesting that negative regulators are limiting. One such negative regulator appears to be the receptor for activated C kinase, Rack (Luo et al, 2015), though its mechanism of activation and action remain to be determined.…”
Section: Regulation Of Src Expression Levels and Activity Are Essentialmentioning
confidence: 99%
“…This phenotype is statistically significant, yet less severe than other RNAi phenotypes for other genes [e.g. brk ; (Luo et al, 2015)]. These results suggest that neo plays a general, previously uncharacterized role in supporting migration in two distinct cell types; further characterization of the similarities and differences between the mechanisms involving neo in CVM and BCs would be an interesting avenue for future study.…”
Section: Resultsmentioning
confidence: 71%
“…Previous studies suggest the monomeric FBS consensus sequence is PyCAAGGPyCPu or PyGAAGGPyCPu (36). Three possible FBSs were predicted in the 3-kb promoter region of Mmp2: GGAAGGTCA (Ϫ2604 to Ϫ2595), AGGCCTTGA (Ϫ2326 to Ϫ2317), and TCAAGGCTG (Ϫ1254 to Ϫ1263) (Fig.…”
Section: Hormonal Control Of Mmp-induced Fat Body Cell Dissociation Imentioning
confidence: 90%